The Seduction of Unreason : The Intellectual Romance with Fascism from Nietzsche to Postmodernism - Wolin, Richard (Book collections on Project MUSE., 2004)
Fifteen years ago, revelations about the political misdeeds of Martin Heidegger and Paul de Man sent shock waves throughout European and North American intellectual circles. Ever since, postmodernism has been haunted by the specter of a compromised past. In this intellectual genealogy of the postmodern spirit, Richard Wolin shows that postmodernism's infatuation with fascism has been widespread and not incidental.